2020
DOI: 10.1002/chir.23231
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of racemic amlodipine using immobilized ionic liquid by solid‐phase extraction

Abstract: In this paper, a novel l‐glutamate based immobilized chiral ionic liquid (SBA‐IL (Glu)) was prepared by chemical bonding method and applied as a solid sorbent for chiral separation of amlodipine. The performance of SBA‐IL (Glu) was investigated for the absorption of (S)‐amlodipine and separation of amlodipine enantiomer. The static experiment showed that equilibrium adsorption was achieved within 80 minutes, and the saturation adsorptions capacity was 12 mg/g. The complex was then packed in a glass chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Correlations between amlodipine uptakes of metal organic frameworks (MOFs) and their (A) pore volumes, (B) largest cavity diameter, (C) pore limiting diameter selected porous materials will be employed as drug carries for antihypertensive amlodipine, it is essential to ensure that the screened MOFs have a high amlodipine uptake capacity. Our results showed that MIL-100, MIL-101, bio-MOF-100, Cu-BTC, IRMOF series, and MOF-74 series can generally outperform traditional amlodipine storage materials such as SBA-IL (12 mg/g), 35 PMAA@mSiO 2 (201 mg/g) 2 ,…”
Section: Amlodipine Uptake Capacity Screeningmentioning
confidence: 76%
“…Correlations between amlodipine uptakes of metal organic frameworks (MOFs) and their (A) pore volumes, (B) largest cavity diameter, (C) pore limiting diameter selected porous materials will be employed as drug carries for antihypertensive amlodipine, it is essential to ensure that the screened MOFs have a high amlodipine uptake capacity. Our results showed that MIL-100, MIL-101, bio-MOF-100, Cu-BTC, IRMOF series, and MOF-74 series can generally outperform traditional amlodipine storage materials such as SBA-IL (12 mg/g), 35 PMAA@mSiO 2 (201 mg/g) 2 ,…”
Section: Amlodipine Uptake Capacity Screeningmentioning
confidence: 76%
“…7 In contrast, the chiral separation or resolution of racemate (a mixture with equal amounts of enantiomers) remains the most commonly used strategy for obtaining optically pure chiral compounds, which mainly include diastereomeric crystallization, [8][9][10] chiral chromatography, 11 chiral liquid-liquid extraction, 12,13 and chiral adsorption. [14][15][16][17] Among them, the adsorption method is universally known for its low cost, high efficiency, simple operation, and recyclability. Therefore, adsorption based on a chiral absorbent is a promising technique for enantiomer separation and has great potential in application to the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Although the asymmetric synthetic approach has made remarkable progress in the last two decades, the accepted highly selective reactions that can provide pure enantiomers on an industrial scale are still limited 7 . In contrast, the chiral separation or resolution of racemate (a mixture with equal amounts of enantiomers) remains the most commonly used strategy for obtaining optically pure chiral compounds, which mainly include diastereomeric crystallization, 8–10 chiral chromatography, 11 chiral liquid–liquid extraction, 12,13 and chiral adsorption 14–17 . Among them, the adsorption method is universally known for its low cost, high efficiency, simple operation, and recyclability.…”
Section: Introductionmentioning
confidence: 99%